Penerapan Assemmblr Edu Berbasis Etnopaedagogi pada Materi Keragaman Budaya Siswa Kelas V SDN Dukuh Menanggal I/424 Surabaya - Azaro, Putri Sofiana; Satianingsih, Rarasaning (Paedagogie, 2026)
This research addresses the need for adaptive and innovative learning strategies in the digital age. The study aimed to investigate the implementation of Assemblr EDU, an Augmented Reality (AR) platform integrated with an ethnopedagogical approach, to teach cultural diversity to fifth-grade students. The primary objective was to describe the implementation of Assemblr EDU and analyze student responses to its use. This research was conducted at SDN Dukuh Menanggal 1/424 Surabaya during the 2025/2026 academic year. Data sources included observations of teacher and student activities, as well as student response questionnaires. Data collection techniques involved direct observation using observation sheets and student response questionnaires. The research instruments included observation sheets of teacher and student activities, as well as student response questionnaires. Data analysis used descriptive quantitative methods, calculating average percentages for observed aspects and student responses. The results showed that the ethnopedagogical-based implementation of Assemblr EDU was effectively implemented, transforming the concept of cultural diversity into a concrete and interactive learning experience. Both teacher and student activities demonstrated excellent performance, with high levels of student engagement, discipline, and enthusiasm. Student responses to Assemblr EDU were overwhelmingly positive, categorized as 'Very Strong' highlighting its benefits for knowledge, understanding, and motivation. The study concluded that this integrated approach significantly improved critical thinking skills and cultural appreciation among students. It is recommended that teachers continue to use Assemblr EDU and integrate local cultural values, and that schools provide adequate technological facilities to support such innovative.